Pengaruh Promosi, Inovasi Produk dan Kualitas Produk Terhadap Keputusan Pembelian Batik Jumputan Maharani Yogyakarta - Paskalia Multi Jiwuk (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2019)
The purpose of this study was to determine the effect of promotion, product innovation, and product quality on purchasing decisions on batik jumputan maharani Yogyakarta. This research belongs to the type of post facto research. The population in this study were consumers of batik jumputan maharani, which amounted to 97 people who were also used as research samples. The data analysis method used is multiple regression analysis which is supported by F (F-Test) and T (T-Test) and classic assumption tests which consist of normality test, multicollinearity test, heterokedacity test. The results of this study indicate that silmutan conclusions promotion variables, product innovation and product quality affect the purchasing decision. In fact, it shows that product quality has a significant effect on purchasing decisions while promotion and product innovation have no significant effect on purchasing decisions.